G635(P) Inaugural national sim-off event: promoting paediatric sim-based education & region wide sim-enthusiasm. (May 2019) - Mallett, P; Junk, C; Laird, E; McNaughten, B; Bourke, T; Thompson, A
Abstract : Context: Simulation-based education is now a well-established part of healthcare education. However, many healthcare teams still experience challenges with providing this due to limited staff engagement. Often, concerns about performing in 'make-belief' simulations and peer-critique inhibit participation and impede sim-based education credentials. Methods: We conceived, designed, facilitated and evaluated the region's inaugural 'Sim-off competition'. This was devised as a fun, educational opportunity to improve knowledge of Paediatric conditions, to aid networking, and act as an inter-speciality and multi-professional event. It was the first National Sim-off competition in any speciality across the UK and Ireland. The contest ran as an informal 'round robin' competition with 10 competing teams representing hospitals from all 5 NI Healthcare trusts, a University APNP team and a Paediatric EM team from Dublin. Our prestigious judging panel comprised of 5 experienced paediatric clinicians with expertise in clinical education. Several moderate complexity scenarios were designed. Team marks were awarded for both technical and non-technical skills. Outcomes: 114 people attended this inaugural event in QUB Riddel Hall on Friday 15th June 2018. There were 44 Paediatric ST1–8 trainees as well as 70 other attendee's. 26 doctors and 20 nurses formed the 10 competing teams. Specialities including General Practice, Anaesthetics, Emergency Medicine and Medical Education were represented in the audience. Feedback was received from 21 participants and 11 observers. 85% of those (27 people) felt that performing simulation as a competition enhanced the educational experience. Some comments included: 'Extremely enjoyable day- competitive side of sim added to the experience', and 'An exemplary day of education. Well done to all involved on an excellent concept!' Conclusions: This inaugural 'sim-off' contest has provided trainees and sim-enthusiasts an ideal opportunity to engage in an informal competition, enhance perceptions of sim-based education and generate region-wide enthusiasm. Following its success, or team has been contacted by colleagues who are organising National and European Paediatric and Simulation conferences to recreate this event at their conference. It is hoped this will be used as a platform for further similar events within different specialities and also run as a biennial event in Paediatrics in Ireland.